Epidemiological Determinants of Underweight, Wasting, and Stunting Among Children Aged 6-59 Months: A Cross-Sectional Study in India - Bhusnurmath, Annadaneshwari B; Rao, Akhila Keshava; Chingale, Ashwini; Karikatti, Shobha (National Journal of Community Medicine, 2025)
Background: Undernutrition is still one of the main reasons for sickness and death in children across the world. In India, even though there are many national nutrition programmes, the problem is still very common. This study was done to find out how widespread undernutrition is among children under five years of age and to understand the main factors causing it, with special focus on the situation in this region. Methods: A cross-sectional study was conducted from February to August 2022 in Belagavi district, Karnataka, among preschool children aged 6 months to 6 years with suspected or confirmed malnutrition. Results: A large number of children were found to be malnourished 81.3% were underweight, 66.3% were stunted and 58.1% were wasted. Children above 12 months of age had a higher chance of being stunted and wasted. Fathers who were literate were less likely to have underweight children and mothers with education seemed to protect their children from wasting. Wasting was more common in children with higher birth order and when the gap between births was more than two years. Babies born with a weight above 2.5 kg and those with full-term gestation had lower chances of being underweight and stunted. Children who had incomplete immunization were more likely to be stunted. Not giving prelacteal feeds was found to reduce the risk of both underweight and stunting, while giving top milk reduced the chances of underweight. Conclusion: This study shows very high levels of undernutrition, especially stunting and wasting, among children under five years in urban India. Factors like parents’ education, birth conditions and feeding practices were found to have a strong effect on children’s nutrition. These results point to the urgent need for focused, local strategies to tackle childhood undernutrition and reduce its harmful impact on health.